1,25-Dihydroxyvitamin D Inhibits Osteoarthritis by Modulating Interaction Between Vitamin D Receptor and NLRP3 in Macrophages [Retraction] - Duan A; Ma Z; Liu W; Shen K; Zhou H; Wang S; Kong R; Shao Y; Chen Y; Guo W; Liu F (Dove Medical Press, 2022)
Duan A, Ma Z, Liu W, et al. J Inflamm Res. 2021;14:6523–6542. The Editor and Publisher of Journal of Inflammation Research wish to retract the published article. Concerns were raised following the authors request to replace images from Figure 2 and Figure 8. It was found that images from several figures within the article appeared to have been duplicated. Specifically, Figure 1, MMP13, OA+Vehicle appears to have been duplicated with Figure 2, ADAMTS5, VDR−/–OA+Vehicle. Figure 2, ADAMTS5, VDR−/–OA+Vitamin D appears to have been duplicated with Figure 2, MMP13, VDR−/–OA+Vehicle. Figure 8, LPS&Nig, Mφ-VDRKD+Vehicle appears to have been duplicated with Figure 8, LPS&Nig, Mφ-VDRKD+1,25VD. In addition, it was also found the image from Figure 5F, Mφ-NCKD, LPS&Nig appears to have been duplicated with Figure 2C, IL-1β+PBS from Duan et al, 2021 (https://doi.org/10.1186/s13287-021-02507-2). The authors did respond to our queries and explained the duplication of images occurred due to the poor management of the original data files. It was determined the duplication of images and admission of poor data management did raise concerns about the validity of the findings and the decision was made to retract the article. The authors agree with this decision. Our decision-making was informed by our policy on publishing ethics and integrity and the COPE guidelines on retraction. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as “Retracted”. This retraction relates to this paper